Here's the question you clicked on:
sha0403
a school has 63 students studying A,B and C. 33 study A, 25 study B, 26 study C. 10 study A and B, 9 study B and C while 8 study both A and C. Equal num study all three subjects as those who learn none of the three. How many study all 3 subjects? #help me solve this question#
|dw:1356287630536:dw| a+b+d+e = 33 b+e+f+c = 25 d+e+f+g = 26 b+e = 10 f+e = 9 d+e = 8 e = 63 - (a+b+c+d) Solve for e..
where do you get e=63-(a+b+c+d)?
It is given that - Equal num study all three subjects as those who learn none of the three. The people who do not study any of them are given by U - (A U B) Here, U = 63 .. And, A U B is given be (a+b+c+d+e) and, I considered the people who study all the three as 'e' And, Sorry, I did a mistake .. I would be -> e = 63 - (a+b+c+d+e)
why u no include f in e=63-(a+b+c+d+e)? can u explain me? i still not understand....
those who learn none of the three subject ----> 63-(a+b+c+d+e+f+g)
i don't know but the answer is 3..
pellet! :P I'm extremely sorry again! :P yeah, you are absolutely correct! - it ought to be 63 - (a+b+c+d+e+f+g)
those who learn none of the three subject = total students - students learning atleast 1 subject, got this ?
those who learn none of the three subject = U - (A U B U C) = 63-(a+b+c+d+e+f+g)
so now did u get how e=63-(a+b+c+d+e+f+g) @sha0403 ?
ook thank u so much u all for helping me...now i get it... ;)